Leucocytes and Thrombosis - Banks, D. C; Mitchell, J. R. A (Thrombosis and Haemostasis, 1973)
Normal white cell adhesiveness was found in a group of patients with idiopathic thrombocytopenia in whom the mean platelet count was 34,000 per cu. mm.Marked elevation of white cell adhesiveness was observed after splenectomy. This did not correlate with changes in the white cell count but did parallel the increase in platelet count and adhesiveness.White cell adhesiveness was increased in patients with a recent myocardial infarction. As it was also increased in patients with other acute illnesses and was normal in patients with old myocardial infarcts, the test is not of diagnostic value in thrombotic disease.